2021
DOI: 10.1007/s00109-021-02113-y
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of DAMPs, TLR4, and proinflammatory cytokines in pulmonary fibrosis

Abstract: Pulmonary fibrosis is a chronic debilitating condition characterized by progressive deposition of connective tissue, leading to a steady restriction of lung elasticity, a decline in lung function, and a median survival of 4.5 years. The leading causes of pulmonary fibrosis are inhalation of foreign particles (such as silicosis and pneumoconiosis), infections (such as post COVID-19), autoimmune diseases (such as systemic autoimmune diseases of the connective tissue), and idiopathic pulmonary fibrosis. The thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 175 publications
(198 reference statements)
0
24
0
1
Order By: Relevance
“…These findings suggested that CCL3 plays an important role in pulmonary inflammation and PF, and that DHA inhibits CCL3 expression to attenuate pulmonary inflammatory responses and PF. fibroblasts, leading to the formation of fibrosis [25]. Furthermore, many cytokines, particularly the IL-6 family, can activate STAT3 rapidly within cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that CCL3 plays an important role in pulmonary inflammation and PF, and that DHA inhibits CCL3 expression to attenuate pulmonary inflammatory responses and PF. fibroblasts, leading to the formation of fibrosis [25]. Furthermore, many cytokines, particularly the IL-6 family, can activate STAT3 rapidly within cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines can either directly activate myofibroblasts or induce the transformation of epithelial cells into fibroblasts, leading to the formation of fibrosis [ 25 ]. Furthermore, many cytokines, particularly the IL-6 family, can activate STAT3 rapidly within cells.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the lungs, cells release DAMPs to alert the innate immune system to begin cell death. In addition, heat shock proteins and high-mobility group Box 1 stimulate mitogen-activated protein kinases and nuclear factor of kappa light polypeptide gene enhancer in B-cells (NF-κB) to activate the inflammatory response (Bolourani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Due to viral infection, systemic inflammation, and coagulation disturbance, tissues are constantly damaged, releasing pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs), including the extracellular molecule adenosine triphosphate (ATP) [ 19 , 38 , 39 ]. Extracellular ATP acts through paracrine and autocrine signaling pathways, acting as a strong “find me” signal for immune cell recruitment to damaged sites [ 40 ].…”
Section: Introductionmentioning
confidence: 99%